Bleeding Follicular Conjunctivitis due to Influenza H1N1 Virus - Maria Jesus Lopez-Prats; Empar Sanz Marco; Juan Jose Hidalgo-Mora; Salvador Garcia-Delpech; Manuel Diaz-Llopis (Journal of Ophthalmology)
Influenza H1N1 or A virus is a new virus serotype capable of human-to-human transmission. This infection causes a flu syndrome similar to that of seasonal influenza, with only one case of conjunctivitis described and no clinical details or microbiological confirmation. Its diagnosis is performed by PCR of pharyngeal smear of the patients affected. We report the first well-documented case in the medical literature of conjunctivitis by H1N1 virus.